Analisis dan Pengujian Quality Assurance pada Landing Page Alpha97 Berbasis Standar Internasional ISO/IEC/IEEE 29119 - Mohamad Ilman; Chairul Anwar (Journal of Information Systems and Business Technology, 2025)
This research evaluates the quality of the Alpha97 e-learning landing page by adopting the ISO/IEC/IEEE 29119 international standard. The study focuses on verifying the functional integrity and reliability of the system through a structured testing life cycle as defined in ISO 29119-2, including the planning, design, and execution phases. Specification-based testing techniques from ISO 29119-4, specifically Equivalence Partitioning and State Transition Testing, were applied to analyze the newsletter subscription forms and mobile navigation mechanisms. Results indicate that core features such as interface responsiveness and interactive elements function correctly according to user requirements. However, the analysis identified weaknesses in the email validation logic and potential performance risks linked to external CDN dependencies. The study concludes that while the platform is functionally sound, improvements in security protocols and self-hosted asset management are necessary to enhance long-term stability and reliability for a better user experience.